Location planning of smart charging station based on fuzzy TOPSIS method. Issue 1 (February 2021) - Zhao, Xuliang; Xue, Jiguang; Zhang, Xiaoqi; Qin, Yuewei; Zhang, Xiaoyi; Yu, Kun
Abstract: With the increasing demand of electric vehicle charging, it is necessary to plan the location of electric vehicle charging station scientifically and reasonably. By considering the intelligent characteristics of unattended smart charging station, this paper studies the location problem of charging station under the influence of multiple factors, and the evaluation index system of smart charging station location is established. In the light of experts' evaluation and a lot of experience, the fuzzy number is adopted to express the evaluation value and corresponding weight of indexes. The technique for order preference by similarity to an ideal solution (TOPSIS) method of multi-criteria decision-making (MCDM) is employed to sort the schemes and select the best one. Finally, the rationality and feasibility of the proposed method are verified by simulation results, and the influence of index weight on scheme selection is analyzed.